Differentiation of osteoblasts: the links between essential transcription factors - Khotib, Junaidi; Marhaeny, Honey Dzikry; Miatmoko, Andang; Budiatin, Aniek Setiya; Chrismawan, Ardianto; Rahmadi, Mahardian; Pratama, Yusuf Alif; Bakhtiar, M. Taher (Taylor & Francis, 2022)
Osteoblasts, cells derived from mesenchymal stem cells (MSCs) in the bone marrow, are cells responsible for bone formation and remodeling. The differentiation of osteoblasts from MSCs is triggered by the expression of specific genes, which are subsequently controlled by pro-osteogenic pathways. Mature osteoblasts then differentiate into osteocytes and are embedded in the bone matrix. Dysregulation of osteoblast function can cause inadequate bone formation, which leads to the development of bone disease. Various key molecules are involved in the regulation of osteoblastogenesis, which are transcription factors. Previous studies have heavily examined the role of factors that control gene expression during osteoblastogenesis, both in vitro and in vivo. However, the systematic relationship of these transcription factors remains unknown. The involvement of ncRNAs in this mechanism, particularly miRNAs, lncRNAs, and circRNAs, has been shown to influence transcriptional factor activity in the regulation of osteoblast differentiation. Here, we discuss nine essential transcription factors involved in osteoblast differentiation, including Runx2, Osx, Dlx5, b-catenin, ATF4, Ihh, Satb2, and Shn3. In addition, we summarize the role of ncRNAs and their relationship to these essential transcription factors in order to improve our understanding of the transcriptional regulation of osteoblast differentiation. Adequate exploration and understanding of the molecular mechanisms of osteoblastogenesis can be a critical strategy in the development of therapies for bone-related diseases.